The Oath Concept: Basis for Dismissal from Office “for Breach of Oath” and System of Guarantees for Labor Rights Protection - Khlystun, Yuliia (Archives of Criminology and Forensic Sciences, 2024)
The specified article studies the oath concepts, “breach of oath”, and the dismissal of a special subject — a judge — on this basis. It emphasizes the importance of ensuring that the norms governing the procedure and process of dismissal from office are effective, taking into account high standards im- posed on judges (both in their appointment to the office and in the adminis- tration of justice), and should serve as a reliable safeguard against wrongful dismissals. Each stage of a disciplinary proceeding involving a judge must uphold labor guarantees of rights security that cannot be violated. The pa- per summarizes that dismissal from office should take place considering the provisions of the Labor Code of Ukraine, along with the norms of special leg- islation defining the status of a judge. In addition, there should be an effective system of guarantees for the protection of labor rights, which should operate in today’s conditions.